Brewer’s Yeast and “Omics” Technologies - Strack, Lysann; Stahl, Ulf (BrewingScience, 2009)
"Omics" technologies comprise genomics, transcriptomics, proteomics and metabolomics; the last three fields are pooled within the notion "functional genomics". In this review, these techniques which concentrate on aspects of the "course from gene to metabolites" nare surveyed especially with regard to bottom-fermenting brewer’s yeasts. ith the aid of these global methods it is possible to combine a collective knowledge of an investigated organism which is necessary to understand the details of its metabolic system. Hence, the challenge is to introduce the above mentioned studies for the determination of targets and approaches for the improvement of yeast organisms. Herein, brewing yeasts are reviewed with concern to the determination of their "ome" levels. But because of the hybrid nature of the brewer’s yeast’s genome problems emerged regarding the "omics"-applicability which are depicted in this paper furthermore.This Minireview is the first section of a two-part publication. The second part with the title "Reduction of diacetyl production by brewer’s yeast" will be published in the next issue of Brewing Science in February 2010.